The dynamics of surges in the 3 February 2015 avalanches in Vallée de la Sionne. Issue 11 (22nd November 2016) - Köhler, A.; McElwaine, J. N.; Sovilla, B.; Ash, M.; Brennan, P.
Abstract: Five avalanches were artificially released at the Vallée de la Sionne test site in the west of Switzerland on 3 February 2015 and recorded by the GEOphysical flow dynamics using pulsed Doppler radAR Mark 3 radar system. The radar beam penetrates the dilute powder cloud and measures reflections from the underlying denser avalanche features allowing the tracking of the flow at 111 Hz with 0.75 m downslope resolution. The data show that the avalanches contain many internal surges. The large or "major" surges originate from the secondary release of slabs. These slabs can each contain more mass than the initial release, and thus can greatly affect the flow dynamics, by unevenly distributing the mass. The small or "minor" surges appear to be a roll wave‐like instability, and these can greatly influence the front dynamics as they can repeatedly overtake the leading edge. We analyzed the friction acting on the fronts of minor surges using a Voellmy‐like, simple one‐dimensional model with frictional resistance and velocity‐squared drag. This model fits the data of the overall velocity, but it cannot capture the dynamics and especially the slowing of the minor surges, which requires dramatically varying effective friction. Our findings suggest that current avalanche models based on Voellmy‐like friction laws do not accurately describe the physics of the intermittent frontal region of large mixed avalanches. We suggest that these data can only be explained by changes in the snow surface, such as the entrainment of the upper snow layers and the smoothing by earlier flow fronts. Key Points: An avalanche's mass can increase many times by secondary releases, which gives rise to major surges Internal surges frequently overtake the leading edge The effective friction varies dramatically between inside the flow and the leading edge